2015
DOI: 10.1097/jto.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Acquired Resistance to AZD9291

Abstract: Acquired resistance mechanisms of AZD9291 in patients with EGFR-mutant NSCLC who failed treatment with first-generation EGFR TKIs include the loss of EGFR-mutant clones plus alternative pathway activation or histologic transformation and EGFR ligand-dependent activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(69 citation statements)
references
References 37 publications
0
67
0
2
Order By: Relevance
“…In vitro analysis demonstrated that FGF2 supplement conferred resistance to osimertinib in EGFR-mutant NSCLC cells [72]. Clinically FGFR amplification after progression on osimertinib were reported after osimertinib [72].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro analysis demonstrated that FGF2 supplement conferred resistance to osimertinib in EGFR-mutant NSCLC cells [72]. Clinically FGFR amplification after progression on osimertinib were reported after osimertinib [72].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically FGFR amplification after progression on osimertinib were reported after osimertinib [72]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the resistance mechanism of EGFR most commonly known. This acquired resistance is mediated by a threonine-to-methionine mutation in EGFR at position 790 (EGFR T790M), activation of a bypass-signalling pathway such as mesenchymal-epithelial transition (MET) pathway, human epidermal growth factor 2 (HER2), or mitogen-activated protein kinase 1 (MAPK1) amplification, and histologic transformation to small-cell lung cancer or an epithelial-to-mesenchymal transition [12][13][14][15]. Following the acquisition of the mutation, the median survival is less than two years, so there is a need to develop new drugs that will control tumor growth in patients positive EGFR T790M.…”
Section: Third Generation Of Egfr Inhibitorsmentioning
confidence: 99%